The Small Regulatory Antisense RNA PilR Affects Pilus Formation and Cell Motility by Negatively Regulating pilA11 in Synechocystis sp. PCC 6803 - Hu, Jinlu; Zhan, Jiao; Chen, Hui; He, Chenliu; Cang, Huaixing; Wang, Qiang (Frontiers in Microbiology, 2018)
Pili are found on the surface of many bacteria and plays important roles in cell motility, pathogenesis, biofilm formation, and sensing and reacting to environmental changes. Cell motility in the model cyanobacterium Synechocystis sp. PCC 6803 relies on expression of the putative pilA9-pilA10-pilA11-slr2018 operon. In this study, we identified the antisense RNA PilR encoded in the noncoding strand of the prepilin-encoding gene pilA11. Analysis of overexpressor (PilR(+)) and suppressor (PilR(–)) mutant strains revealed that PilR is a direct negative regulator of PilA11 protein. Although overexpression of PilR did not affect cell growth, it greatly reduced levels of pilA11 mRNA and protein and decreased both the thickness and number of pili, resulting in limited cell motility and small, distinct colonies. Suppression of PilR had the opposite effect. A hypothetical model on the regulation of pilA9-pilA10-pilA11-slr2018 operon expression by PilR was proposed. These results add a layer of complexity to the mechanisms controlling pilA11 gene expression and cell motility, and provides novel insights into how sRNA and the intergenic region secondary structures can work together to discoordinatly regulate target gene in an operon in cyanobacterium.